Applying Iterative Method to Solving High-Order Terms of Seafloor Topography. Issue 1 (2nd January 2020) - Fan, Diao; Li, Shanshan; Meng, Shuyu; Lin, Yi; Xing, Zhibin; Zhang, Chi; Yang, Junjun; Wan, Xiaoyun; Qu, Zhenhao
Abstract: We introduce an iterative inversion method to address the problems in high-order seafloor topography inversion using gravity data (gravity anomaly and vertical gravity gradient anomaly), such as the difficulty in computing the equation and the uniqueness of the calculation results. A part of the South China Sea is selected as the experimental area. Considering the coherence and admittance function of gravity topography and vertical gravity gradient topography, the inversion band of the gravity anomaly and vertical gravity gradient anomaly in the study area is 30 km–120 km. Seafloor topography models of different orders are constructed using an iterative method, and the performance of each seafloor topography model is analyzed against ETOPO1 and other seafloor topography models. The experimental results show that as the inversion order increases, the clarity and richness of seafloor topographic expression continuously improve. However, the accuracy of seafloor topography inversion does not improve significantly when the inversion order exceeds a certain value, which is related to the contribution of high-order seafloor topography to gravity information. The results show that the accuracy of BGT4 (inversion model constructed by the gravity anomaly) is slightly poorer than that of BVGGT4 (inversion model constructed by the vertical gravity gradient anomaly) in areas with complex topography, such as multi-seamounts and trenches, and the results are generally better in areas with flat seafloor topography.